A meta-requirement approach to validate user requirement specification : Threshold definition - Muhamad Idaham, Umar Ong; Mohamed Ariff, Ameedeen (Institute of Electrical and Electronics Engineers Inc., 2023)
The software requirement specification document is critical for ensuring that software development projects are completed on time, within budget, and meet the needs of all stakeholders. User requirement completeness refers to the extent to which user requirements accurately and fully capture the needs and expectations of stakeholders for a given system or application. The completeness of user requirements is critical for the successful design and implementation of information systems, as incomplete requirements can lead to a range of issues, including system failure, delays, and cost overruns. The author has developed a meta-requirement validation approach to validate the completeness of a set of requirements. Based on a numerical reading, the user of the approach will be able to determine the completeness of the requirement. This publication's main objective is to identify the threshold value through a method of literature search. The identified threshold value will be used to determine the minimum reading for the result to be deemed complete. The result of a 70% value has been identified to be suitable for the use of the validation approach.